2019
DOI: 10.1038/s41467-019-11730-8
|View full text |Cite
|
Sign up to set email alerts
|

Syringeable immunotherapeutic nanogel reshapes tumor microenvironment and prevents tumor metastasis and recurrence

Abstract: The low response rate of current cancer immunotherapy suggests the presence of few antigen-specific T cells and a high number of immunosuppressive factors in tumor microenvironment (TME). Here, we develop a syringeable immunomodulatory multidomain nanogel (iGel) that overcomes the limitation by reprogramming of the pro-tumoral TME to antitumoral immune niches. Local and extended release of immunomodulatory drugs from iGel deplete immunosuppressive cells, while inducing immunogenic cell death and increased immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
71
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(74 citation statements)
references
References 63 publications
0
71
0
Order By: Relevance
“…The anti-CD47 and CPMV acted synergistically to combat tumor growth. And just recently, we demonstrated the synergistic effects of combining CPMV with checkpoint inhibitors, such as anti-programmed cell death-1 [120].…”
Section: Vlps In Combination Therapymentioning
confidence: 99%
“…The anti-CD47 and CPMV acted synergistically to combat tumor growth. And just recently, we demonstrated the synergistic effects of combining CPMV with checkpoint inhibitors, such as anti-programmed cell death-1 [120].…”
Section: Vlps In Combination Therapymentioning
confidence: 99%
“…By provoking a CD8+ T cell response through medullary macrophages, the CHP-based vaccine was proved the promising immunotherapeutic effect in animal models [136]. Unlike the directed induction of apoptosis or autophagy by the cytotoxic drugs, vaccine adjuvants or immunomodulators typically trigger antitumor immunity by regulating the tumor microenvironment [137][138][139]. However, the limitations of tumor immunotherapy include the high cost of therapy, the difficulty of sustained systematic immunity, and low patient response.…”
Section: Combinatorial Chemo-immunotherapymentioning
confidence: 99%
“…International Publisher revealed that many solid tumors are associated with immune cell infiltration in the tumor immune microenvironment (TIME) which affects therapy efficacy and overall survival to no small extent [7][8][9]. A study revealed that high T-cell subsets density in gastric cancer was associated with prolonged survival [10].…”
Section: Ivyspringmentioning
confidence: 99%